2020
DOI: 10.1136/thoraxjnl-2020-214993
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal cannula oxygen therapy to treat patients with hypoxemic acute respiratory failure consequent to SARS-CoV-2 infection

Abstract: This observational study aims to assess the outcome and safety of O2-therapy by high-flow nasal cannula (HFNC) in 28 consecutive patients with severe hypoxemic acute respiratory failure (hARF) consequent to SARS-CoV-2 infection, unresponsive to conventional O2-therapy. Nineteen patients had a positive response. Nine patients required escalation of treatment to non-invasive ventilation (five subsequently intubated). None of the staff had a positive swab testing during the study period and the following 14 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
1
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 7 publications
4
87
1
8
Order By: Relevance
“…The study by Wang et al 14 showed that none of the patients with PaO 2 /FiO 2 > 200 mm Hg had HFNC failure compared to 63% failure in patients with low PaO 2 /FiO 2 (≤ 200 mm Hg). Additionally, the RR was found to decrease signi cantly after 1-2 hours of HFNC in the successful cases [13].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The study by Wang et al 14 showed that none of the patients with PaO 2 /FiO 2 > 200 mm Hg had HFNC failure compared to 63% failure in patients with low PaO 2 /FiO 2 (≤ 200 mm Hg). Additionally, the RR was found to decrease signi cantly after 1-2 hours of HFNC in the successful cases [13].…”
Section: Discussionmentioning
confidence: 90%
“…Our study adds to the existing knowledge by showing the potential utility of the previously established cutoff of ROX index for monitoring HFNC treatment in COVID-19-related AHRF. Another study showed that PaO 2 /FiO 2 ≤ 100 mm Hg at ICU admission was a signi cant predictor of HFNC failure [13]. The study by Wang et al 14 showed that none of the patients with PaO 2 /FiO 2 > 200 mm Hg had HFNC failure compared to 63% failure in patients with low PaO 2 /FiO 2 (≤ 200 mm Hg).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Das Therapieversagen unter nicht-invasiver Behandlungsstrategie bei COVID-19 schwankt erheblich. Für High-Flow werden Versagerquoten von 32,2 % [65]…”
Section: Bildgebungunclassified